Economics - Byrns, Ralph T.; Stone, Gerald W. (Glenview, Il : Scott, Foresman & Co., 1981)
As in previous editions, Slavin introduces more math review than other products to help students get past math phobias through consistent practice. Matched with the extensive learning aids available in Connect Plus, including the adaptive study tool LearnSmart, Slavin provides a complete learning environment for the introductory economics student.
Cataloging based on CIP information.
Originally published: Santa Monica, Calif. : Goodyear Pub. Co., c1981.
Includes bibliographical references and index.
aia 04/05/2018
Loans
Keywords: Economics